Insecticidal activity of 1.8-cineole against Plodia interpunctella (Hbn.) (Lepidoptera Pyralidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
A solution of 1.8-cineole (purity ≥ 98%) was tested. Insects were exposed to the active ingredient for 24 hours. The percentage of hatched eggs was detected after 6 days from the treatment; larvae and adults mortality was observed after 24 and 48 hours. 330 μl/l air of 1.8-cineole causes 95% mortality of Plodia interpunctella eggs. II and IV instar larvae show different tolerances to the active ingredient. DL95 value, recorded after 48 hours, is 23.67 μl/l air for II instar larvae, while it doubles for male and female IV instar larvae. Adult females are more resistant to the active ingredient (DL50 adults ♂ ♂ : 0.31 μl/l air and DL50 adults ♀ ♀: 0.38 μl/l air; DL95 ♂ ♂: 7.46 μl/l air and DL95♀ ♀: 8. 70 μl/l air).
Keywords: Eucalyptol; Indian Meal Moth; mortality